Menyelami Konsep dan Nilai-nilai HAM dalam Perspektif Hukum Islam - Nurma Harana Mora Siregar; Sakinah Azzahra Hsb; Uswatun Hasanah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the Islamic perspective on Human Rights (HR) through a qualitative approach based on literature review. It emphasizes that the principles of human rights are not foreign to Islamic teachings, but are inherently embedded in the values of Sharia derived from the Qur'an and Hadith. Islam upholds justice, freedom of religion, equality, the right to life, and social and economic welfare. The article also examines contemporary challenges faced by Muslim societies in implementing human rights, such as gender inequality, restrictions on religious freedom, and the marginalization of vulnerable groups, including the LGBT community. The findings reveal that the tensions between Islamic principles and international human rights standards often stem from differing normative foundations and interpretations of individual freedom. Therefore, a contextual reinterpretation (ijtihad) is necessary to ensure that Islamic values remain relevant and responsive to modern global challenges. The study concludes that, when applied wisely and aligned with universal humanitarian values, Islamic teachings hold significant potential to contribute to the development of a just, inclusive, and dignified society.